HUMANISM BUILDING THROUGH ARTS EDUCATION IN INDUSTRIAL ERA 4.0 - Musthofa Kamal (Jurusan Sastra Indonesia, 2020)
In the millennial era, cloud computing technology is an information technology that plays an important role in industrial and business operations. The use of big data technology applications and IoT (Internet of Things). On the one hand, advances in information technology have helped many human activities. On the other hand, advances in information technology lead to the lifestyles of people who tend to be individualistic and cool with their own world, causing behavior that ignores the surrounding environment. Art has a great opportunity as an educational medium to re-instate a sense of humanism. Humanism education at its core has the purpose of how it can be humanized, so education is considered successful while learners can understand themselves and their environment. Through performing arts, they are trained in body language, breathing, sound, and taste. Also, as an art community, the performers are trained in cooperation, mutual respect, social sensitivity, and more. The experience of branding is expected to be a meaningful learning medium for the culprit. One of the benefits of learning activities that are integrated with the performing arts is to train a sense of humanism. Performing arts are creative arts that involve the actors to act, imagine, and reflect on individual experiences in their artistic or non-artistic activities. That is, performing arts activities are activities that require the participation of individuals intellectually, emotionally, physically, verbally, and socially. Art education can be linked to various things because it is itself a multidisciplinary activity. The range of the motion of art education not only refers to the education of aspiring artists. Art education is more than just creating and understanding art and aesthetics but uses it in the context of humanist education. Therefore, art education may be able to provide spiritual discourse, morals, and pragmatic skills that are the basis of human life and living.